“SUPPLYING THE DEFAULTS OF NATURE BY THE INDUSTRY OF ART”: NATURA, ARS AND EXERCITATIO IN APHRA BEHN’S THE DUMB VIRGIN; OR, THE FORCE OF IMAGINATION - Torralbo Caballero, Juan de Dios (Revista Internacional de Culturas y Literaturas, 2016)
Se investigan los conceptos de natura y ars que informan The Dumb Virgin de Behn. Se destaca la conciencia artística del poeta, en términos de mímesis y representación, revelando el conocimiento del autor de las teorías poéticas, así como su implementación en la historia a través de un protagonista que, sin poder hablar, es un pintor magistral, complementado además por el la hermana del protagonista, deformada pero elocuente. Abstract It investigates the concepts of natura and ars that inform Behn’s The Dumb Virgin. It is highlighted the poet’s artistic conscience, in terms of mimesis and representation, revealing the author’s knowledge of poetical theories, as well as their implementation in the story through a protagonist who, while unable to speak, is a masterful painter, further complemented by the protagonist’s sister, who is deformed but eloquent.